Pengaruh Kepemimpinan, Kompetensi dan Budaya Organisasi Terhadap Kinerja Dosen Berbantuan Sofware SPSS - Pristiyanilicia Putri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
This study aims to reveal: Influence Leadership, Competence, and Cultural Organization partially and imultan to the performance of lecturers STMIK / AMIK Royal Kisaran. The population of this study are all lecturers on campus STMIK / AMIK Royal Kisaran which amounted to 82 people. The analytical method used by using regression analysis and data was processed using SPSS software aid Version 20. The result of multiple regression analysis showed that: (1) In partial leadership obtained t value> from t table (6,284> 1,664) with significant level (0,00 from t table (4,869> 1,664) with significant level (0,00 from t table (7,814> 1,664) with significant level (0,00